The Role of Mindfulness in Managing Academic Stress: Implications for Student Well-being and Mental Resilience - Achmad Roziqin; Isnaini Khoirotun Ni'mah; Achmad Riza Fauzi; Normiwati Binti Barwi (Education and Sociedad Journal, 2025)
This study aims to explore the implementation of mindfulness in reducing students' academic stress in junior high school and to assess its long-term impact on students' emotional well-being and mental health. This research departs from students' increasing academic stress, which often hurts their emotional well-being. Mindfulness programs involving breathing exercises and meditation are expected to help students manage academic stress and develop mental resilience. This study uses a qualitative approach with a descriptive design, collecting data through interviews, observations, and documentation from students, teachers, and principals. The data was then analyzed using the Miles and Huberman approach. The findings show that mindfulness programs have succeeded in reducing students' academic stress and anxiety and improving their emotional well-being. In addition, mindfulness also has a long-term impact by helping students develop mental resilience to face future challenges. The results of the study hopefully can provide benefits that mindfulness can be applied in elementary schools as a preventive effort to reduce academic stress, as well as encourage the development of a more comprehensive educational curriculum that prioritizes student welfare as well as providing insights for the development of education policies that integrate mindfulness in the teaching and learning process.